Treatment Optimization Through Refinement of a Conceptual Site Model Using Compound Specific Isotope Analysis. Issue 1 (17th December 2015) - Smith, Gregory; Wang, Yi
Abstract : Two adjacent automotive component manufacturers in Japan had concentrations of trichloroethene (TCE) and perchloroethene (PCE) in soils and groundwater beneath their plants. One of the manufacturers extensively used these solvents in its processes, while the adjacent manufacturer had no documentation of solvent use. The conceptual site model (CSM) initially involved a single source that migrated from one building to under the adjacent building. Further, because low concentrations of daughter products (e.g., cis‐1, 2‐dichloroethene; 3.6 to 840 micrograms per liter [μg/L]) were detected in groundwater, the CSM did not consider intrinsic degradation to be a significant fate mechanism. With this interpretation, the initial remedial design involved both source treatment and perimeter groundwater control to prevent offsite migration of the solvents in groundwater. Identifying whether intrinsic degradation was occurring and could be quantified represented a means of eliminating this costly and potentially redundant component. Further, incorporating intrinsic degradation into the remediation design would also allow for a more focused source treatment, resulting in further cost savings. Three rounds of sampling and data interpretation applying compound specific isotope analysis (CSIA) were used to refine the CSM. The first sampling round involved three‐dimensional CSIA ( 13 C, 37 Cl, and 2 H), while the second two rounds involved 13 C only, focusing on degradation over time. For the May 2012 sampling, δ 13 C for PCE ranged from –31‰ to –29.6 ‰ and for TCE ranged from –30.4‰ to –28.3‰; showing similar values. δ 2 H for TCE ranged from 581‰ to 629‰, indicating a manufactured TCE rather than that resulting from dehalogenation processes from PCE. However, mixing of manufactured TCE with that resulting from degraded PCE cannot be ruled out. Because of the similar δ 13 C ratios for PCE and TCE, and 37 Cl data for PCE and TCE, fractionation and enrichment factors could not be relied upon. Fractionation patterns were evaluated using graphical methods to trace TCE to the source location to better focus the locations for steam injection. Graphical methods were also used to define the degradation mechanism and from this, incorporate intrinsic degradation processes into the remedial design, eliminating the need for a costly perimeter pump and treat system. ©2015 Wiley Periodicals, Inc.